Juvenile homicide in England and Wales - Condry, Rachel (The Routledge international handbook of juvenile homicide, 2024)
In England and Wales, children aged 10–17 years who commit a crime are considered “youth” or “juvenile” offenders and are dealt with by the Youth Justice System, although there are also distinctive sentencing provisions and guidelines for young adults aged 18–24 years. In recent years, there have been serious concerns over the volume and proportion of homicides involving young people, with 16- to 24-year-olds accounting for 40% of perpetrators (ONS, 2022). In this chapter, we disaggregate a decade of national data for England and Wales, collated in the Homicide Index, to focus on homicides perpetrated by juvenile offenders between 2010 and 2020. Our analysis of juvenile homicide incident and perpetrator characteristics is contextualized by a discussion of the law, criminal justice processes, and sentencing of juvenile offenders in England and Wales.